Invalid women : figuring feminine illness in American fiction and culture, 1840-1940 - Price Herndl, Diane, 1959- (University of North Carolina Press, 1993)
In this imaginative work of cultural and literary history, Diane Price Herndl examines the tensions found in literary representations of feminine illness. Using medical texts, art, and advertising as well as major works of fiction, Price Herndl argues that such representations were not "natural" but were instead ideologically motivated. While invalid women in American fiction sometimes upheld and sometimes challenged dominant social and medical practice, Price Herndl contends that the discourse of feminine illness was a battleground for powerful forces that sought to define women's role in society even after feminism's emergence. The figure of the invalid female must, she says, be understood as a highly politicized figure. Price Herndl looks first at mid-nineteenth-century medical theories that defined women as fundamentally "invalid." She then turns to important literary texts, including works by Harriet Beecher Stowe, E.D.E.N. Southworth, Laura Curtis Bullard, Washington Irving, Edgar Allan Poe, and Nathaniel Hawthorne, to show that male and female authors represented invalid women differently. Price Herndl contends that the figure of the ill woman conveniently resolved problems of the changing culture for nineteenth-century authors of both sexes. Price Herndl then traces the image of invalid women from the turn of the century to World War II, using texts by Charlotte Perkins Gilman, Edith Wharton, Ellen Glasgow, Henry James, F. Scott Fitzgerald, and Tillie Olsen, as well as the film Dark Victory. Despite dramatic changes in both medical practices and women's place in society, fictional representations remained strikingly stable and politically conservative, Price Herndl argues, even when the author's intent was otherwise